Augmented Reality and Transversal System of Teaching-Learning to teach anatomy - Pereira, Adalberto Bosco Castro; Santos, Igor Nascimento Guanais; Alves, Luan Felipe Cruz; Eberhard, Anne (Anais do Workshop de Informática na Escola (WIE); 2020: Anais do XXVI Workshop de Informática na Escola, 2020)
This paper deals with initial results by using Augmented Reality and Transversal System of Teaching-Learning (TSTL) to teach anatomy in an undergraduate course of Physical Education. The ongoing project aims to use existing and low-cost resources in lessons to promote accessibility and school inclusion. The resources needed for this research are smartphones in the perspective of BYOD (Bring Your Own Device) and VR cardboards as an optional feature to increase immersion. This research is qualitative, and its methodology is grounded in action-research. Analysis of data collected were based in the theory of Structural Cognitive Modifiability (SCM) of Reuven Feuerstein.